The Tradition of Kembar Mayang in Javanese Traditional Weddings: A Philosophical Study of the Purwosari Batanghari Nuban Society of East Lampung - Didik Kurniawan; Muhammad Syaifullah (Journal of Research in Islamic Education, 2022)
Philosophical approach in religious studies trying to find an explanation of the concept of religious teachings by check and find the system of reason understandable. Understanding Islam through a philosophical approach is intended to give meaning to something that is encountered, to capture the wisdom, essence or essence contained in Islamic teachings so that in performing acts of worship you do not feel empty. The philosophical approach is likened to an analytical knife to dissect Islam in depth, integrally and comprehensively to give birth to understanding and thoughts about Islam that are always relevant at every time and space. The method used in this study is empirical normative using a descriptive approach qualitative. This article aims to find out about the Mayang Twin Tradition, which is a cultural custom that has been passed down from generation to generation from their ancestors and continues to be carried out by the community around the current culture, especially in rural areas. In tradition Kembar mayang of course still maintain the principles of monotheism, justice, freedom, please help and maintain human benefit. The values contained in the mayang twin ransom tradition are a form of tawasul which is positioned as a means of endeavor (wasilah) to ask Allah and still believe in the fact that only Allah alone has absolute qudrah in everything.